Effect of mediterranean diet on non-alcoholic fatty liver disease (NAFLD) - Walczak, Patrycja; Walczak, Klaudia; Zdun, Sylwia; Nemeczek, Sylwia; Merkisz, Konrad; Grzybowski, Jakub; Marciniak, Agnieszka; Grzywna, Natalia; Jaskuła, Karolina; Orłowski, Władysław (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the work: Non-alcoholic fatty liver disease (NAFLD) is a common condition in the general population. In its course, excessive fatty acids are deposited in liver cells. The best way to prevent it is to reduce weight by being physically active and eating a proper low-calorie diet. The purpose of this study is to describe the potential health benefits of the mediterranean diet in people with NAFLD. For this purpose, the literature available in the PubMed database was reviewed using the following keywords: mediterranean diet; non-alcoholic fatty liver disease (NAFLD); non-alcoholic steatohepatitis (MASH). State of the knowledge: The mediterranean diet is rich in fruits, vegetables, nuts, fish, olive oil and whole-grain products. It has the effect of decreasing insulin resistance, which is a major cause of NAFLD. In addition, it exerts anti-inflammatory and antioxidant properties. In recent years, numerous clinical studies have been conducted analyzing the effects of this diet on laboratory results, liver steatosis and progression to steatohepatitis (MASH) in patients with NAFLD. Conclusions: The results of the studies show that following a mediterranean diet can prevent as well as alleviate the course of this disease. However, there is a need for more clinical studies, on larger groups of people to recognize the mediterranean diet as an effective form of NAFLD therapy.